STUDI KOMPARATIF PENETAPAN PERUBAHAN JENIS KELAMIN BAGI PEMOHON PASCA TRANSISI GENDER (STUDI PENETAPAN NOMOR: 195/PDT.P/2021/PN.JKT.UTR DAN PENETAPAN NOMOR: 30/PDT.P/2022/PN PWT) - Dara Santari; Rosnidar Sembiring; Syarifah Lisa Andriati (Smart Education, 2026)
Gender change is a legal phenomenon that has generated debate in the Indonesian legal system, particularly regarding the recognition of legal identity for applicants after gender transition. The main problem in this study lies in the absence of legal regulations that specifically and comprehensively regulate the procedures, requirements, and legal consequences of gender change, resulting in disparities in court decisions. This study aims to analyze the legal vacuum related to gender change in Indonesia, the legal consequences of determining gender change on population administration, and to comparatively analyze the judges' considerations in Decision Number: 195/Pdt.P/2021/PN.Jkt.Utr and Decision Number 30/Pdt.P/2022/PN.Pwt. The research method used is normative legal research with a statutory approach, a conceptual approach, and a case approach. The research results show that the regulation of gender reassignment in Indonesia is still limited to aspects of population administration, as stipulated in Article 56 paragraph (1) of Law Number 23 of 2006 concerning Population Administration in conjunction with Law Number 24 of 2013. The absence of substantive regulations causes judges to rely on legal findings in deciding gender reassignment requests. The legal consequences of gender reassignment include changes in population identity, civil legal status, and implications for marriage and inheritance. In Decision Number 195/Pdt.P/2021/PN.Jkt.Utr, the judge used a progressive, human rights-based approach, resulting in the granting of the request. Whereas in Decision Number 30/Pdt.P/2022/PN.Pwt, the judge used a normative, moral, and religious approach, resulting in the rejection of the request. This disparity demonstrates the lack of legal certainty regarding gender reassignment in Indonesia.